The Inquisitive Eye - Fineman, Mark B. (Oxford University Press, 1981)
Keywords: Problems, exercises, etc; Visual perception; Visual perception; dept.psy; faculty_collection

Premorbid social competence and the revolving door phenomenon in psychiatric hospitalization - Marsh, A.; Glick, M.; Zigler, E. (Journal of Nervous and Mental Disease, 1981)
The relation between premorbid social competence and length of initial hospitalization was examined in 381 male state hospital patients in four diagnostic categories: Schizophrenic, affective reaction, psychoneurotic, and personality disorder. A significant relation was discovered between diagnosis and outcome, with schizophrenic patients having the longest and personality disorder patients the shortest lengths of initial hospitalization. Premorbid social competence was related to outcome, as assessed both by length of initial hospitalization, and by whether the patient was rehospitalized. These two outcome measures were found to be positively related, thus supporting the developmental formulation that premorbid social competence is indicative generally of prognosis. The findings were employed to generate the inference that patients at differing levels of premorbid social competence require different treatment modalities. © 1981 by The Williams & Wilkins Co.
Keywords: Adult; Hospitals, Psychiatric; Human; Length of Stay; Male; Mental Disorders; Mood Disorders; Neurotic Disorders; Personality Disorders; Recurrence; Schizophrenia; Social Adjustment; central nervous system; dept.psy; major clinical study; mental hospital; personality disorder; schizophrenia; sociology